Association Between the Health Locus of Control and Medication Adherence: An Observational, Cross-Sectional Study in Primary Care - Hanna-Maria E. Gerland; Tino Prell; Tino Prell (Frontiers in Medicine, 2021)
Background: Medication non-adherence is an important healthcare issue and a common problem. Many predictors of non-adherence have been found in different settings and cohorts.Objective: Evaluate the impact of the health locus of control (HLC) on unintentional/intentional non-adherence in primary care.Methods: In this observational, cross-sectional study, 188 patients (mean age 63.3 ± 14.9 years) were recruited from three primary care practices in Jena, Germany, over 4 months. The study assessed demographic data, self-reported adherence (German Stendal adherence to medication score, SAMS), HLC, and depression.Results: According to the SAMS total score, 44 (27.5%) were fully adherent, 93 (58.1%) were moderately non-adherent, and 23 (14.4%) were clinically significantly non-adherent. The most common reasons for non-adherence were forgetting to take the medication or lacking knowledge about the prescribed medication. Multiple linear regression revealed that adherence was good in people with external HLC and poor in internal HLC. In particular, intentional non-adherence was positively associated with internal HLC and negatively with fatalistic external HLC. Depression had a negative influence on both intentional and unintentional non-adherence.Conclusion: HLC is an independent predictor of medication non-adherence and is a promising target for interventions that enhance adherence.